Plankton and oceanographic time-series - Sheppard, Lawrence; Defriez, Emma; Reid, Philip; Reuman, Daniel (Dryad Digital Repository, 2019)
This zip file includes annualized Plankton Colour Index time-series, annualized plankton species abundance time-series, and annualized oceanographic variables. See readme.txt file.